The impact of bank capital on economic activity - evidence from a mixed-cross-section GVAR model - Marco Gross; Christoffer Kok; Dawid Żochowski (European Central Bank (ECB), 2016)
We develop a Mixed-Cross-Section Global Vector Autoregressive (MCS-GVAR) model for the 28 EU economies and a sample of individual banking groups to study the propagation of bank capital shocks to the economy. We conduct various simulations with the model to assess how capital ratio shocks influence bank credit supply and aggregate demand. We distinguish between contractionary and expansionary deleveraging scenarios and confirm the intuitive result that only when banks choose to achieve higher capital ratios by shrinking their balance sheets would economic activity be at risk to contract. The model can be used to establish ranges of impact estimates for capital-related macroprudential policy measures, including counter-cyclical capital buffers, systemic risk buffers, G-SIB buffers, etc., also with a view to assessing the cross-country spillover effects of such policy measures. We highlight the importance for macroprudential policy makers to give clear guidance to banks as to how certain macroprudential policy measures should be implemented – depending on what measure is considered, during which phase in the business cycle, and for what particular purpose.
Keywords: C33; E51; E58; 330; euro area money markets; financial crisis; network analysis; spatial regressions